First-Line Treatment for Advanced SCLC: What Is Left Behind and Beyond Chemoimmunotherapy - Giunta, Emilio Francesco; Addeo, Alfredo; Rizzo, Alessio; Banna, Giuseppe Luigi (Frontiers in Medicine, 2022)
Small cell lung cancer (SCLC) is still a lethal disease. Three phase III randomized clinical trials (IMpower133, CASPIAN, and KEYNOTE-604) have highlighted the survival gain of adding immune checkpoint inhibitors to first-line standard chemotherapy in advanced SCLC patients. In this review, we discuss the data from the three trials above. Furtherly, we analyze issues that still need to be elucidated, like the role of biomarkers, poor performance status at baseline, the presence of brain metastases, and the platinum compound's choice. Moreover, we depict the future of SCLC first-line therapy management, focusing on new therapeutic strategies currently under investigation.